Desarrollo de las cooperativas agropecuarias del noreste de Misiones, Argentina - Godoy, Antonia Elisabeti; Martínez, Mirta Claudia; Carvallo Krieger, María Alejandra; Pokolenko, Ana Alicia; Tarnoski, Sergio Oscar; Dip, Juan (Cooperativismo & Desarrollo, 2014)
This article is a product of the research project “The impact of management models on the developmentof agricultural cooperatives in northeast Misiones”, conducted in Universidad Nacional de Misiones, Argentina, between 2010 and 2012. It was based on information from documentary and empirical sourcesfrom surveys and interviews conducted with 80% of the population under study, founding members ofagricultural cooperatives, and key informants. The aim was to identify the critical factors that hinderedgrowth and, based on these, determine the key areas for reactivating and generating sustainable develop-ment in these cooperatives. It was corroborated that 90% of the cooperatives surveyed were in a state of“invisibility”, with a high level of economic inactivity caused by the circumstances they were created in,and the absence of a common project.
Keywords: human capital; agricultural cooperatives; local development; management; policies